Production and purity of phycobiliproteins from selected marine and freshwater cyanobacteria subjected to different drying methods - Begum, Hasina; Khatoon, Helena; Md. Yusoff, Fatimah; Mohamed Din, Mohamed Shariff (Asian Fisheries Society, 2020)
Phycobiliproteins, light-harvesting pigments found in cyanobacteria, red algae and cryptomonad are gaining importance in food, nutraceutical and pharmaceutical industries. Thus, a sustainable source of phycobiliproteins production is an essential consideration in meeting the increasing demand for these natural pigments. The present work aimed to compare the concentration and purity of phycobiliproteins from marine (Geitlerinema sp. and Synechococcus sp.) and freshwater (Oscillatoria sp. and Spirulina sp.) cyanobacteria, when subjected to different drying methods viz. sun-drying, oven-drying and freeze-drying. Results showed that the three different drying methods influenced the concentration and purity of phycobiliproteins from the different cyanobacteria. Under oven drying condition, phycocyanin concentration (mg.mL-1 ) was significantly higher (P < 0.05) in marine Geitlerinema sp. followed by Oscillatoria sp. Synechococcus sp. and Spirulina sp., respectively, compared to sun-drying and freezedrying methods. Phycoerythrin and allophycocyanin concentrations were also significantly higher (P < 0.05) in marine periphytic Geitlerinema sp. when compared to other cyanobacteria subjected to oven drying. In addition, results from oven-dried marine periphytic Geitlerinema sp. showed that total phycobiliproteins production and purity ratio of phycocyanin were significantly higher (P < 0.05) in comparison to sun-drying or freeze-drying Spirulina sp., Synechococcus sp. and freshwater Oscillatoria sp.